Qualitative analysis of the Dix-Hallpike maneuver in multi-canal BPPV using a biomechanical model: Introduction of an expanded Dix-Hallpike maneuver for enhanced diagnosis of multi-canal BPPV - Henri Traboulsi (KeAi Communications Co., Ltd., 2017)
Introduction/Objective: Multiple canal BPPV can be a diagnostic challenge to the clinician. This is due in part to the complex anatomy of the labyrinth but also to complex and often simultaneous ocular responses that result from stimulation of multiple canals during traditional diagnostic testing. Our objective was to analyze the Dix-Hallpike maneuver used in the diagnosis of BPPV to look for patterns of simultaneous canal response and to develop a diagnostic maneuver that will allow separation of canal responses in multiple canal BPPV. Methods: A previously created and published 3D biomechanical model of the human labyrinths for the study of BPPV was used to analyze and compare the position and movement of otoliths in the Dix-Hallpike maneuver as well as in a proposed expanded version of the traditional Dix-Hallpike maneuver. Results: The traditional Dix-Hallpike maneuver with the head hanging may promote movement of otoliths in 5 of the six semicircular canals. The Dix-Hallpike maneuver with the head lowered only to the horizontal position allows for otoconia in only the lowermost posterior canal to fall to the most gravity dependent position. This position allows for minimal or no movement of otoconia in the contralateral posterior canal, or in either superior canal. Turning the head ninety degrees to the opposite side while still in the horizontal position will provoke otolith movement in only the contralateral posterior canal. The superior canals can then be examined for free otolith debris by extending the neck to a head-hanging position. These positions may be assumed directly from one to the next in the lying position. There seems to be no advantage to sitting up between positions. Conclusion: The Dix–Hallpike maneuver may cause simultaneous movement of otoliths present in multiple canals and create an obstacle to accurate diagnosis in multi-canal BPPV. An expanded Dix-Hallpike maneuver is described which adds intermediate steps with the head positioned to the right and left in the horizontal position before head-hanging. This expanded maneuver has helped to isolate affected semi-circular canals for individual assessment in multiple canal BPPV.